Public awareness regarding children vaccination in Jordan - Masadeh, Majed M (Hum Vaccin Immunother, 2014)
Immunization can contribute to a dramatic reduction in number of vaccine-preventable diseases among children. The aim of this study is to investigate mothers’ awareness about child vaccines and vaccination in Jordan. This study was a community-based, cross-sectional study that was performed at public places in Irbid City. Data was collected from 506 mothers. After verbal approval, mothers were interviewed to assess their knowledge, attitudes, and practice toward vaccination. Results show that majority of mothers had acceptable knowledge and positive attitude toward vaccination. Most of mothers (94.7–86.8%) were able to identify vaccines that are mandatory as per the national vaccination program. Lower knowledge was observed among mothers (71.6%) for HIB vaccination being mandatory. Most mothers (97.2%) had vaccination card for their baby form the national vaccination programs. Vaccination delay was reported by about 36.6% of mothers and was shown to be associated with significantly (P = 0.001) lower vaccination knowledge/attitude score. Additionally, mothers who reported to be regularly offered information about vaccination during visits and those who identified medical staff members as their major information source had significantly higher vaccination knowledge/attitude score (P = 0.002). In conclusion, vaccination coverage rate is high; however, some aspects of knowledge, attitudes, and practice of vaccination need to be improved. Knowledge and attitudes of mothers were directly associated with their practice of vaccination. Medical staff education about vaccination during each visit seems to be the most effective tool that directly reflects on better practice of vaccination such as reducing the possibility for vaccination delay.